2010
DOI: 10.1107/s1600536810001819
|View full text |Cite
|
Sign up to set email alerts
|

Bis(4-bromobenzoyl)(2,7-dimethoxynaphthalene-1,8-diyl)dimethanone

Abstract: Key indicators: single-crystal X-ray study; T = 296 K; mean (C-C) = 0.004 Å; R factor = 0.038; wR factor = 0.103; data-to-parameter ratio = 14.5.In the title compound, C 26 H 18 Br 2 O 4 , the two 4-bromobenzoyl groups at the 1-and 8-positions of the naphthalene ring system are anti to each other. The dihedral angle between the two benzene rings is 50.92 (14) . The dihedral angles between the two benzene rings and the naphthalene ring system are 70.18 (11) and 74.98 (12) . A weak intermolecular C-HÁ Á ÁO h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…The aromatic rings in this molecule are clarified to be assembled with non-coplanar configuration resulting in partial disruption of π-conjugated ring systems. Recently, we reported the X-ray crystal structures of 1,8-diaroylated 2,7-dimethoxynaphthalenes such as 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene (Nakaema et al, 2007), 1,8-dibenzoyl-2,7-dimethoxynaphthalene (Nakaema et al, 2008), bis(4-bromophenyl) (2,7-dimethoxynaphthalene-1,8-diyl)dimethanone (Watanabe et al, 2010a), (Watanabe et al, 2010b) and 1,8-bis(4-methylbenzoyl)-2,7-dimethoxynaphthalene (Muto et al, in press). As a part of our continuous study on the molecular structures of this kind of homologous molecules, the X-ray crystal structure of title compound, (I), a peri-aroylnaphthalene bearing amino groups, is discussed in this article.…”
Section: Commentmentioning
confidence: 98%
“…The aromatic rings in this molecule are clarified to be assembled with non-coplanar configuration resulting in partial disruption of π-conjugated ring systems. Recently, we reported the X-ray crystal structures of 1,8-diaroylated 2,7-dimethoxynaphthalenes such as 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene (Nakaema et al, 2007), 1,8-dibenzoyl-2,7-dimethoxynaphthalene (Nakaema et al, 2008), bis(4-bromophenyl) (2,7-dimethoxynaphthalene-1,8-diyl)dimethanone (Watanabe et al, 2010a), (Watanabe et al, 2010b) and 1,8-bis(4-methylbenzoyl)-2,7-dimethoxynaphthalene (Muto et al, in press). As a part of our continuous study on the molecular structures of this kind of homologous molecules, the X-ray crystal structure of title compound, (I), a peri-aroylnaphthalene bearing amino groups, is discussed in this article.…”
Section: Commentmentioning
confidence: 98%
“…For electrophilic aromatic substitution of naphthalene derivatives, see: Okamoto & Yonezawa (2009). For related structures, see: Mitsui, Nakaema et al (2008); Mitsui, Noguchi et al (2009); Watanabe, Nakaema, Muto et al (2010); Watanabe, Nakaema, Nishijima et al (2010); Hijikata et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…In the course of our study on electrophilic aromatic aroylation of 2,7-dimethoxynaphthalene, peri-aroylnaphthalene compounds have proven to be formed regioselectively with the aid of suitable acidic mediators (Okamoto & Yonezawa, 2009). Recently, we reported the crystal structures of several 1,8-diaroylated naphthalene homologues exemplified by bis(4-bromobenzoyl)(2,7-dimethoxynaphthalene-1,8-diyl)dimethanone (Watanabe, Nakaema, Muto et al, 2010). The aroyl groups at the 1,8-positions of the naphthalene rings in these compounds are twisted almost perpendicularly but the benzene ring moieties of the aroyl groups tilt slightly toward the exo sides of the naphthalene rings.…”
Section: S1 Commentmentioning
confidence: 99%
“…Fang et al [ 4 ] synthesis, biocharbon (biochar) and biocharbon-based materials in the removal of environmental pollutants, hydrogen production and carbon dioxide capture were summarized and compared. Shoji et al [ 5 ] studied the compound C 26 H 18 Br 2 O 4 , and concluded that the dihedral angle between the two benzene rings is 50.92 (14)° and a weak intermolecular C–H⋯O hydrogen bond exists between the methyl group and the carbonyl O atom. Gordon et al [ 6 ] studied The Crystal Structure of Bis-( m -chlorobenzoyl)-methane by three anisotropic least squares refinement and concluded that the structure confirms conclusions from the structure of bis (m-Bromobenzoyl) methane where the symmetry of the molecule was forced by the crystal symmetry.…”
Section: Introductionmentioning
confidence: 99%